PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP MOTIVASI BELAJAR FISIKA SISWA SMA NEGERI 2 BANDA ACEH - Elisa, Elisa; Nadila, Mutiara Elsa; Nurulwati, Nurulwati (Journal of Technology and Literacy in Education, 2025)
Low student motivation is often caused by a mismatch between learning materials and students’ needs and characteristics. To address this, a learning model that enhances student engagement is necessary, such as Problem-Based Learning (PBL). This study aims to determine the effect of the PBL model on students’ motivation to learn physics at SMA Negeri 2 Banda Aceh. The research sample consisted of two Grade X classes selected through purposive sampling: the experimental class used the PBL model, while the control class used the Discovery Learning model. Data were collected using validation sheets, observation sheets, tests, and motivation questionnaires. Data analysis employed a t-test using Welch’s t-test. The results showed that the t-value was greater than the t-table (8.608 > 2.000), leading to the rejection of H₀ and acceptance of Hₐ. Therefore, the implementation of the PBL model had a significant effect on students’ learning motivation compared to the learning model used in the control class.